Monitoring serum CEA in women with primary breast tumours positive for oestrogen receptor and with spread to lymph nodes. - van der Linden, J C (1985)
Serum carcinoembryonic antigen concentrations (serum CEA) in 80 patients with primary breast cancer were measured preoperatively, one month after operation, and thereafter serially every third month. These data were related to histological and morphometric features of the primary breast carcinoma and the lymph node metastases and to clinical follow up data. Analysis of the serum CEA values showed significant correlations with size of tumour, the presence of lymph node metastases, oestrogen receptor, and occurrence of distant metastases. Furthermore, the results indicated that serial determination of serum CEA in the first two years after operation may be useful in monitoring for the occurrence of distant metastases in patients with metastatic spread to lymph nodes and with large (greater than or equal to 2 cm) primary breast tumours positive for oestrogen receptor. In agreement with other studies, however, it was found that the predictive value of serum CEA concentrations in general is weak and costs may prohibit the implementation of the routine assessment of CEA concentrations.